Wide area circumferential ablation for pulmonary vein isolation using radiofrequency versus laser balloon ablation - Jamario Skeete; Parikshit S. Sharma; David Kenigsberg; Grzegorz Pietrasik; Ahmed F. Osman; Venkatesh Ravi; Jeanne M. Du‐Fay‐de‐Lavallaz; Zoe Post; Jeremiah Wasserlauf; Timothy R. Larsen; Kousik Krishnan; Richard Trohman; et al. (Journal of Arrhythmia, 2022)
Abstract Background Persistent atrial fibrillation (AF) is associated with high recurrence rates of AF and atypical atrial flutters or tachycardia (AFT) postablation. Laser balloon (LB) ablation of the pulmonary vein (PV) ostia has similar efficacy as radiofrequency wide area circumferential ablation (RF‐WACA); however, an approach of LB wide area circumferential ablation (LB‐WACA) may further improve success rates. Objective To evaluate freedom from atrial tachyarrhythmia (AFT/AF) recurrence postablation using RF‐WACA versus LB‐WACA in persistent AF patients. Methods This was a retrospective multicenter study. Patients were followed for up to 24 months via office visits, Holter, and/or device monitoring. The primary endpoint was freedom from AFT/AF after a single ablation procedure. Secondary endpoints included freedom from AF, freedom from AFT, first‐pass isolation of all PVs, and procedural complications. Results Two hundred and four patients were studied (LB‐WACA: n = 103; RF‐WACA: n = 101). Patients’ baseline characteristics were similar except patients in the RF‐WACA group were older (64 vs. 68, p = .03). First‐pass isolation was achieved more often during LBA (LB‐WACA: 88% vs. RF‐WACA 75%; p = .04). Procedure (p = .36), LA dwell (p = .41), and fluoroscopy (p = .44) time were similar. The mean follow‐up was 506 ± 279 days. Sixty‐six patients had arrhythmic events including 24 AFT and 59 AF recurrences. LB‐WACA group had higher arrhythmia‐free survival (p = .009) after single ablation procedures. In the multivariate Cox regression model, RF‐WACA was associated with a higher recurrence of AFT compared with LB‐WACA (Adjusted HR 3.16 [95% CI: 1.13–8.83]; p = .03). Conclusions LB‐WACA was associated with higher freedom from atrial arrhythmias mostly driven by the lower occurrence of AFT compared with RF‐WACA.